Role of Economic Diplomacy for Development - Shrestha, Madhavji (NCWA Annual Journal, 2023)
This paper discusses the role of economic diplomacy in the development of Nepal with special reference to its neighboring countries and other developed countries. An underdeveloped country like Nepal, should aspire for comprehensive and progressive growth and development to enhance its international image and promote its specific identity for becoming a self-reliant country. Implementable and good national policies led by wise political leadership and efficient bureaucratic set-up are highly needed. Good understanding and appropriate evaluation of the existing ambiance of the national demands and needs must be taken into account by the national leadership for conducting economic diplomacy. The writer has used information from various secondary data sources including books, journals, periodicals, and online media in the process of writing this paper.